2016
DOI: 10.1111/jcmm.13014
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐apoptotic Noxa is involved in ablative focal irradiation‐induced lung injury

Abstract: Although lung injury including fibrosis is a well‐documented side effect of lung irradiation, the mechanisms underlying its pathology are poorly understood. X‐rays are known to cause apoptosis in the alveolar epithelial cells of irradiated lungs, which results in fibrosis due to the proliferation and differentiation of fibroblasts and the deposition of collagen. Apoptosis and BH3‐only pro‐apoptotic proteins have been implicated in the pathogenesis of pulmonary fibrosis. Recently, we have established a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…On the other hand, the activation of MDA5 by Semliki Forest virus induces both caspase-9-mediated apoptosis and caspase-8-mediated extrinsic apoptosis (27). Since ionizing radiation can modulate the intrinsic and extrinsic apoptotic pathway (28)(29)(30)(31), further studies are needed to clarify the apoptotic pathway which RLR agonist and ionizing radiation cooperatively activate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the activation of MDA5 by Semliki Forest virus induces both caspase-9-mediated apoptosis and caspase-8-mediated extrinsic apoptosis (27). Since ionizing radiation can modulate the intrinsic and extrinsic apoptotic pathway (28)(29)(30)(31), further studies are needed to clarify the apoptotic pathway which RLR agonist and ionizing radiation cooperatively activate.…”
Section: Discussionmentioning
confidence: 99%
“…Pmaip1 is a pro-apoptotic Bcl-2 homology domain 3-only protein [ 31 ]. It has been demonstrated that the Pmaip1-mediated pathway plays an important part in IR-induced apoptotic response [ 41 , 42 , 43 ]. Pmaip1 knockout mice showed resistance to IR-induced intestinal crypt cell apoptosis and survived longer than WT mice [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PM014 is an effective drug for reducing irradiated mediated fibroblast differentiation. In our previous study, we identified a new molecular mechanism underlying IR-induced fibrosis by demonstrating that Noxa-induced apoptosis plays an important role in fibrosis 22 . As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured on coverslips coated with poly- L -lysine, fixed with 4% paraformaldehyde in PBS and permeabilised with 0.1% Triton X-100 22 . The cells were incubated with primary antibodies at 4 °C overnight, and then stained with secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation